Energy-efficient dynamic wavelength and bandwidth allocation algorithm with delay constraint for time and wavelength division multiplexed passive optical networks - Cunqian YU; Mingzhu TANG; Rongxi HE (Tongxin xuebao)
Based on offline scheduling and node modular design,an energy-efficient dynamic wavelength and bandwidth allocation algorithm with the delay constraint (EE-DWBA-DC) was proposed.Optical line terminal (OLT) and optical network units (ONU) were considered to save energy.Under the constraint of packet delay,the number of active wavelengths could be reduced as much as possible and the length of polling cycle was increased.At the same time,the uplink and downlink transmission time of OLT and ONU were concentrated to reduce the state conversion times and extend its low-power duration.In addition,the high energy consumption voids of channels were attempted to be minimized.The simulation results verify that the proposed algorithm can reduce the energy consumption of OLT and ONU and the total energy consumption of the whole network under the premise of guaranteeing packet delay constraints.